METHODOLOGY OF DEFENCE OF STATE INFORMATIVE RESOURCES. COMPARATIVE ANALYSIS OF BASIC TERMS AND DETERMINATIONS - Юдін, Олександр Костянтинович; Бучик, Сергій Степанович (Ukrainian Information Security Research Journal, 2015)
The comparative analysis of basic terms and determinationswhich are certain in obedience to leading documentsin relation to security of informative resources and enteredby authors in previous researches is carried out in the article.To such terms and determinations it is taken authorsand examined in the article: state informative resources,threat to the state informative resources, national informativeresources, national electronic informative resources,system of national informative resources, system of stateinformative resources, state electronic informative resources,register of electronic state informative resources,depositary of electronic state informative resources, attackon state informative resources, method of double three ofsecurity, threat of normatively-legal aspiration, threat oforganizational aspiration, threat of technical aspiration,identifier of object. These terms and determinations aresuggested to put in basis of standard or normative documentof technical protection in relation to terminology inindustry of security of state informative resources.